Root traits as drivers of plant and ecosystem functioning: current understanding, pitfalls and future research needs. Issue 3 (15th January 2021) - Freschet, Grégoire T.; Roumet, Catherine; Comas, Louise H.; Weemstra, Monique; Bengough, A. Glyn; Rewald, Boris; Bardgett, Richard D.; De Deyn, Gerlinde B.; Johnson, David; Klimešová, Jitka; Lukac, Martin; McCormack, M. Luke; et al.
Summary: The effects of plants on the biosphere, atmosphere and geosphere are key determinants of terrestrial ecosystem functioning. However, despite substantial progress made regarding plant belowground components, we are still only beginning to explore the complex relationships between root traits and functions. Drawing on the literature in plant physiology, ecophysiology, ecology, agronomy and soil science, we reviewed 24 aspects of plant and ecosystem functioning and their relationships with a number of root system traits, including aspects of architecture, physiology, morphology, anatomy, chemistry, biomechanics and biotic interactions. Based on this assessment, we critically evaluated the current strengths and gaps in our knowledge, and identify future research challenges in the field of root ecology. Most importantly, we found that belowground traits with the broadest importance in plant and ecosystem functioning are not those most commonly measured. Also, the estimation of trait relative importance for functioning requires us to consider a more comprehensive range of functionally relevant traits from a diverse range of species, across environments and over time series. We also advocate that establishing causal hierarchical links among root traits will provide a hypothesis‐based framework to identify the most parsimonious sets of traits with the strongest links on functions, and to link genotypes to plant and ecosystem functioning.